Working conditions and personal characteristics: Predicting burnout among dental professionals in Mysore, India: A questionnaire survey - Swati Harilal Chainani; Siddana Sunitha; CVK Reddy; Maurya Manjunath; Sushma Rudraswamy (Wolters Kluwer Medknow Publications, 2015)
Introduction: Dentistry is a profession demanding physical and mental efforts. Increased workload, stress, poorer mental health, and reduced job satisfaction, these factors might combine, to increase the level of "burnout" among dental practitioners. Aim: To assess the burnout level among the dentist practising in Mysore city and to investigate the association between personal characteristics, working conditions and burnout. Materials and Methods: The study was conducted in the month of August-September 2011. A predesigned and pretested questionnaire of 22 items called Maslach Burnout Inventory - Human service Survey was distributed among the dentists to assess the burnout levels. The response was obtained using a Likert scale ranging from 0 to 6. Statistical analysis was carried out using Microsoft Excel and SPSS version 17 (SPSS Inc., Chicago, IL, USA). The data were subjected to mean, standard deviation, and contingency coefficient test at 5% level of significance. Results: Emotional exhaustion was found to be high in 31 (22.1%), moderate in 16 (11.4%), and low in 93 (66.4%) of the dentists. High level of personal accomplishment was found in 63 (45.0%), moderate in 45 (32.1%), and low in 32 (22.9%) dentists. Depersonalization was found to be low in 63 (45.0%), moderate in 45 (32.1%), and high in 32 (22.9%) participants. Conclusion: Of the 140 participants, 16 (11.4%) were found to be at a high risk. 118 (84.3%) in moderate risk and 6 (4.3%) in low risk of burnout.